CONTENT ANALYSIS ON ENGLISH SKILLS FOR THE FUTURE FOR SENIOR HIGH SCHOOL/ ALIYAH GRADE XI LANGUAGE AND CULTURE PROGRAM - Anita Anita; Rina Fitriana (Jurnal Scientia, 2023)
The aim of the research was to find out that “English Skills for the Future” met the evaluation criteria according to experts. Data collected by designing evaluation criteria that contained standard criteria for evaluating English textbooks and explaining its relevance to the 2013 English curriculum material. The researcher found that it met 66.7% of the criteria for English as a Foreign Language (EFL). ). There are eight criteria, namely (1) goals and approaches, (2) design and organization, (3) language content, (4) skills, (5) topics, (6) methodology, (7) practical considerations, and (8) instructions. Then, 33.3% of these textbooks do not meet the criteria of a good EFL textbook. It is categorized as "good" by achieving an average score of 90% of criteria determined by the National Education Standards Agency. The seven cretaria classified as "good" based on the suitability of the material with competency standards and basic competencies (83.3%), material accuracy (83.3%), learning support materials (90%), language accuracy (100%), presentation techniques (100%), teaching and learning techniques (100%), and presentation coverage (81.8%). And also the analyzed English textbooks are relatively relevant to the curriculum 2013. Therefore, it is hoped that teachers can complement some of these deficiencies with other materials to achieve the goals targeted in the 2013 curriculum.